Pollutant Levels Comparison in Tofu Industrial and Domestic Wastewater in Ternate City (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2020)
Tofu industry wastewater have become important issues that arise in line with the increasing in human population and the development progress. Tofu industry is one of the fast growing industries in Indonesia, this causes an increase in the amount of waste of tofu industry in Indonesia, especially in Ternate (Asadiya Karnaningroem, 2018). The purpose of this study was to determine Comparison of pollutant levels in tofu industrial wastewater and Domestic Wastewater in Ternate City. The sample of this research was 1 litre of tofu industrial wastewater and 1 litre domestic wastewater. This type of research is analytic descriptive. This research was conducted at Chemistry laboratory at health polytechnic of ternate and university of unkhair. The test results of tofu wastewater showed that the TSS parameters were 416 mg / L, TDS 1,389 mg / L, DO 4 ppm, pH 7 and BOD 62.8 mg / L. Meanwhile, Tests result of domestic wastewater shows that TDS 839 mg / L, TSS 379 mg / L DO 5.4 ppm, pH 10 and BOD 49.6 mg / L. in conclusion, tofu wastewater has worse quality compared to domestic wastewater. It is recommended that the tofu industry can take the initiative in treating the wastewater produced before disposing it into the environment